Optical sensor for fast and accurate lung cancer detection with tissue autofluorescence and diffuse reflectance spectroscopy - Xianbei Yang; Anzhi Chen; Kaicheng U; Sophia Meixuan Zhang; Peihao Wang; Zheng Li; Yi Luo; Yong Cui (Thoracic Cancer)
Abstract Background Cancer is a severe threat to human health, and surgery is a major method of cancer treatment. This study aimed to develop an optical sensor for fast cancer tissue. Methods The tissue autofluorescence spectrum and diffuse reflectance spectrum were obtained by using a laboratory‐developed optical sensor system. A total of 151 lung tissue samples were used in this ex vivo study. Results Experimental results demonstrate that tissue autofluorescence spectroscopy with a 365‐nm excitation has better performance than diffuse reflectance spectroscopy, and 63 of 64 test samples (98.4% accuracy) were correctly classified with tissue autofluorescence spectroscopy and our developed data analysis method. Conclusions Our promising ex vivo study results show that the developed optical sensor system has great promise for future clinical translation for intraoperative lung cancer detection and other applications.